Feasibility of high-intensity training in asthma. Issue 1 (1st January 2018) - Toennesen, L. L.; Soerensen, E. D.; Hostrup, M.; Porsbjerg, C.; Bangsbo, J.; Backer, V.
ABSTRACT: Background: High-intensity interval training is an effective and popular training regime but its feasibility in untrained adults with asthma is insufficiently described. Objective: The randomized controlled trial 'EFFORT Asthma' explored the effects of behavioural interventions including high-intensity interval training on clinical outcomes in nonobese sedentary adults with asthma. In this article we present a sub analysis of data aiming to evaluate if patients' pre-intervention levels of asthma control, FEV1, airway inflammation and airway hyperresponsiveness (AHR) predicted their training response to the high-intensity interval training program, measured as increase in maximal oxygen consumption (VO2 max). Design: We used data from the EFFORT Asthma Study. Of the 36 patients randomized to the 8-week exercise intervention consisting of high-intensity training three times per week, 29 patients (45% females) completed the study and were included in this data analysis. Pre-intervention assessment included the asthma control questionnaire (ACQ), spirometry, fractional exhaled nitric oxide (FeNO) and AHR to mannitol. VO2 max was measured during an incremental cycle test. Results : The majority of included patients had partly or uncontrolled asthma reflected by a mean ( SD ) ACQ at 1.7 (0.6). Median (IQR) FeNO was 28.5 (23.8) ppb and 75% had a positive mannitol test indicating AHR. The association between patients' training response measured as increase in VO2 max and pre-intervention ACQ scores was not statistically significant ( p  = 0.49). Likewise, the association between patients' increase in VO2 max and FeNO as well as AHR was not statistically significant ( p  = 0.80 and p  = 0.58). Conclusions : Included asthma patients could adhere to the high-intensity interval protocol and improve their VO2 max regardless of pre-intervention levels of asthma control, airway inflammation and AHR.